2022
DOI: 10.1139/cjfas-2021-0327
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for spatiotemporal shift in demersal fishery management priority areas in the western Mediterranean

Abstract: Marine Protected Areas (MPAs) are a promising management tool for the conservation and recovery of marine ecosystems, as well as fisheries management. MPAs are generally established as permanent closures but marine systems are dynamic, which has generated debate in favour of more dynamic designs. As a consequence, the identification of priority areas should assess their persistence in space and time. Here, we develop a step-by-step approach to assess the spatiotemporal dynamics of fisheries management priority… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…In the Ebro Delta margin, a FRA proposal was endorsed by the SAC in 2021 as technically robust (FAO, 2021b). Our analysis, in coherence with other EFHs analysis in the area (DeLaHoz et al, 2018; Paradinas et al, 2022; Scientific Technical and Economic Committee for Fisheries, 2022a) and local knowledge (Bastari et al, 2022), supports this area as a priority area for management.…”
Section: Discussionsupporting
confidence: 85%
“…In the Ebro Delta margin, a FRA proposal was endorsed by the SAC in 2021 as technically robust (FAO, 2021b). Our analysis, in coherence with other EFHs analysis in the area (DeLaHoz et al, 2018; Paradinas et al, 2022; Scientific Technical and Economic Committee for Fisheries, 2022a) and local knowledge (Bastari et al, 2022), supports this area as a priority area for management.…”
Section: Discussionsupporting
confidence: 85%
“…The density maps and annual COGs produced with VAST help distinguish between the areas of the study region where the species of interest is faring well from the areas where the species is undergoing depletion. Such information is invaluable for guiding spatial management efforts, including the design of marine protected areas (Grüss, Biggs, et al., 2019; Paradinas et al., 2022). To further understand the patterns of spatial density and distribution shifts predicted by VAST and better exploit this information, we recommend research to determine the relative importance of fishing, environmental variables and multispecies interactions in explaining changes in density and distribution shifts in starry ray and cod, noting that both are boreal species that may have responded to increasing sea temperatures (Dulvy et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…SC-GAMs are based on the same statistical framework as GAMs and we used them due to their capacity to constrain the functional response curve of the fitted effects to shapes that are in agreement with the niche theory [4]. Despite bathymetry being a well-known environmental driver for hake [7, 9, 10], it could also mask the effect of other more dynamic environmental variables, thus was left behind in the model selection process.…”
Section: Methodsmentioning
confidence: 99%
“…European hake recruits are known to have a marked bathymetric preference to the 150-200m bathymetric strata [7, 9], while adults show a broader bathymetric preference up to 350m deep [10]. However, after a literature review under the SeaWise project and to the best knowledge of the authors, no clear environmental relationships had been found prior to this study, probably due to the restricted spatial scale of most studies.…”
Section: Introductionmentioning
confidence: 97%